Leadership Characteristic Development Model of Chief Police Station Officers under Provincial Region 3 - Sanguansak, Mongkhon; Bhoomkhokrak, Prayad (Ratchaphruek Journal, 2014)
This research aimed to 1) study the leadership characteristics of heads of police stations under Provincial Police Bureau Region Three, 2) create a model for the development of the leadership characteristics of heads of police stations and 3) assess the appropriateness and the possibility of the model for the development of the leadership characteristics of the police station heads under Provincial Police Bureau Region Three as well as its implementation guidelines and present the model. The research consisted of 5 steps: 1) studying the leadership characteristics of police station heads who had passed, with distinction, the assessment under the “Police Station for People” Developmental Project, 2) synthesizing and selecting the appropriate topics which required developing and synthesizing the leadership characteristics of heads of police stations, 3) creating a model for the development of the leadership characteristics of the police stationheads, 4) assessing theappropriateness and the possibility of the actual implementation of the model for the development of the leadership characteristics of police stationheadsand 5) concluding and disseminating the model for the leadership characteristicdevelopment through the publication of the handbook for the leadership characteristicdevelopment of police stationheads. Research tools were a questionnaire, an assessment form and an interview form on the appropriateness and the possibility of the model implementation. 228 police station headsunder Provincial Police Bureau Region Three were research samples, deriving purposively. Statistics used for data analysis were percentage, mean, standard deviation and content analysis. Research findings showed that 1) 62 leadership characteristics of heads of police stations under Provincial Police Bureau Region Threepassed with distinction, the assessment under the “Police Station for People” developmental project in 2012 were divided into 5 aspects by namely, personality, virtue and discipline enhancement, justice facilitation, service for people and technology, 2) the model for the leadership characteristicdevelopmentsof heads of police stations consisted of 4 parts; 2.1) concepts and regulatory principles of the model, 2.2) the general objectives, 2.3) five developmental steps of the leadership characteristics of police stationheads: preparation, assessment prior to the development, assessment after the development and the re-development and 2.4) the implementation guidelines of the model, 3) the assessment through the interviews with expert-level qualified people generally agreed on the appropriateness and the possibility of the implementation of the model for the development of the leadership characteristics of police stationheadsunder Provincial Police Bureau Region Three.